MENGEMAS BISNIS PERHOTELAN DALAM KONSEP SYARIAH - Hartini, Sri (Solidaritas, 2019)
Abstract This study will focus on highlighting the application of Hilal-1 sharia concept in Hotel of Sharia Zaen Solo. This study aimed to describe and analyze the application sharia concept in Hotel of Sharia Zaen Solo based on guidelines for the Implementation of Sharia Hotel businesses contained in the regulations of the Ministry of Tourism and Th Creatif Economy No. 2 in 2014. The results of this study show that Sharia Zaen Hotel has not met the criteria for the sharia hotel business of Hilal-1 because there are severals aspects of products, services, and management that have not been fulfilled such as the facility of massage, sport, and kitchen.Keyword: Halal Tourism, sharia hotel, goverment